SENYAWA STEROID PADA DAUN GAYAM (Inocarpus fagiferus Fosb) DAN AKTIVITASNYA SEBAGAI ANTIOKSIDAN TERHADAP DIFENILPIKRIL HIDRAZIL (DPPH) - I Gusti Agung Putu Surya Adi Krisna; Sri Rahayu Santi; Ni Luh Rustini (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
This research aimed to identify steroid compound from leaf of gayam (Inocarpus fagiferus Fosb) and test its antioxidant activity. Dried leaf powder of gayam was extracted with 5000 mL of 96% ethanol to yield 28,05 g concentrated extract. This extract was then fractionated into n-hexane and choloform to yield 14,18 g n-hexane and 2,21 g choloform fractions respectively. The test using Lieberman Burchard reagent showed that both fractions contain steroid, but n-hexane fraction contained more steroid than chloroform fraction. Separation of n-hexane fraction was done using silica gel column chromatography with n-hexane : ethanol (7:3) as eluent and four groups of fraction were obtained. Fraction F1 contained steroid and was relatively pure therefore it was then identified. The infrared and ultraviolet-visible spectra suggest that the isolate (F1 fraction) has functional groups such as O-H, C=O, C-H, and unconjugated C=C and showed lmax at 279,407, and 669 nm. The antioxidant test showed that the isolate had antioxidant activity toward DPPH with IC50 of 4 ppm.